2006
DOI: 10.1590/s1415-47572006000100029
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mutagenicity in somatic and germ cells of mice submitted to subchronic treatment with an extract of Croton cajucara Benth. (Euphorbiaceae)

Abstract: The plant Croton cajucara Benth. (Euphorbiaceae) is a medicinal plant from the Brazilian Amazon where it is commonly known as sacaca. The principal compound isolated from C. cajucara stem-bark extracts is the clerodane-type diterpene trans-dehydrocrotonin (DCTN) which presents several biological activities, including antiulcerogenic, anti-inflammatory, hypoglycemic, antimutagenic and antitumoral activity. However, few studies have been carried out to evaluate the therapeutic potential of raw C. cajucara extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
(29 reference statements)
0
8
0
6
Order By: Relevance
“…As discrepâncias nos resultados morfométricos verificados em vários estudos que utilizaram agentes quimioterapêuticos para o câncer se devem às diferenças entre as dosagens e esquemas de administração da droga, espécies, linhagens e idade dos modelos experimentais. SANTOS et al (2006) trataram camundongos com 150 mg/kg de peso corpóreo de ciclofosfamida e não observaram efeitos tóxicos nos animais.…”
Section: Discussionunclassified
“…As discrepâncias nos resultados morfométricos verificados em vários estudos que utilizaram agentes quimioterapêuticos para o câncer se devem às diferenças entre as dosagens e esquemas de administração da droga, espécies, linhagens e idade dos modelos experimentais. SANTOS et al (2006) trataram camundongos com 150 mg/kg de peso corpóreo de ciclofosfamida e não observaram efeitos tóxicos nos animais.…”
Section: Discussionunclassified
“…A species belonging to this section, Croton cajucara Benth., popularly known as ''sacaca'' (from the Tupi language, sake'ka, which means ''witchcraft'' or ''spellcasting' ';Le Cointe, 1934), has historically been used in the Amazon region to treat diarrhea, diabetes, liver and kidney problems, to lower cholesterol, and for weight loss (Salatino et al, 2007). Guided by the traditional ethnobotanical uses of C. cajucara, numerous researchers have explored the phytochemical and pharmacological properties of this species (Carvalho et al, 1996;Farias et al, 1997;Maciel et al, 1998aMaciel et al, , 1998bSouza-Brito et al, 1998;Grynberg et al, 1999;Lemos et al, 1999;Hiruma-Lima et al, 1999a;Maciel et al, 2000;Campos et al, 2002;Hiruma-Lima et al, 2002;Maciel et al, 2002;Grassi-Kassisse et al, 2003;Rosa et al, 2003;Alviano et al, 2005;Brito et al, 2006;Santos et al, 2006;Souza et al, 2006;Perazzo et al, 2007). The effectiveness of C. cajucara at reducing lipid and glucose levels has been demonstrated in the laboratory by several authors (Farias et al, 1996(Farias et al, , 1997Costa et al, 1999;Grynberg et al, 1999;Hiruma-Lima et al, 1999b;Maciel et al, 2000;Silva et al, 2001aSilva et al, , 2001b.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlipidemic mice treated with CcB bark aqueous infusion had the level of triglycerides reduced and the level of cholesterol redistributed (3) . In vivo studies confirmed that t-DCTN is not genotoxic nor cytotoxic to mice bone marrow cells (1,25) .…”
Section: Introductionmentioning
confidence: 71%
“…In fact, Santos et al (25) evaluated the genotoxic activity of methanolic extract of CcB bark using the micronucleus assay in Swiss albino mice treated once a week with three extract concentrations (312.5; 625 and 1,250 mg kg -1 i.g.) for 28 days.…”
Section: Discussionmentioning
confidence: 99%